A unique case of perforated bilateral parietal bone thinning in a Third Intermediate Period Egyptian mummy (Geneva Museum D 0242)*. Issue 1 (January 2014) - Seiler, Roger; Rühli, Frank
Since the early nineteenth century, the Museum of Art and History in Geneva has held the mummy of the Lady Tjes-Mut-peret with her coffin (Third Intermediate Period). The mummy was unwrapped in 1824 and the detailed description of this operation mentions several pathological findings. A CT scan was performed in the University Hospital in Geneva in 2011 allowing for the findings of 1824 to be reinterpreted and complemented by the diagnosis of a bilateral parietal bone thinning of the skull.